1984
DOI: 10.1177/027112148400300405
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Written Language to Deaf Infants and Preschoolers

Abstract: The acquisition of oral and written language in six deaf infants is compared from ages one and two years for periods of four and five years. The results indicate: (1) Acquisition of written language is not dependent on oral language; (2) Written language teaching can be initiated at about one year of age; and (3) Written language is easier to learn than oral language. These results suggest that written language instruction in early life helps deaf infants acquire language.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Two studies involved the sight word learning of young deaf children. Suzuki and Notoya (1984) trained 6 mothers to teach their oral deaf children, who were between the ages of 1 and 3 at the outset of the study, to identify words matched with objects, pictures, or actions. After 45 months, the researchers found that the children's written vocabulary was significantly greater than their spoken vocabulary.…”
Section: Effectiveness Of Instructional Approachesmentioning
confidence: 99%
“…Two studies involved the sight word learning of young deaf children. Suzuki and Notoya (1984) trained 6 mothers to teach their oral deaf children, who were between the ages of 1 and 3 at the outset of the study, to identify words matched with objects, pictures, or actions. After 45 months, the researchers found that the children's written vocabulary was significantly greater than their spoken vocabulary.…”
Section: Effectiveness Of Instructional Approachesmentioning
confidence: 99%
“…Calderon and Low [ 98 ] conducted a sub-analysis of a larger study of Early Childhood Home Instruction and found non-significant improvements in language when a father was present at the intervention. Three studies looked at language communication using a longitudinal design; Oral Language Training [ 99 ]; Central Institute for the Deaf Early Education Project [ 100 ]; A Good Future for Deaf Children Programme [ 101 ], and all found improvements in language and communication for the child. There were also 6 papers that reported results from either case or file review, or case studies, all reporting improvements for the child’s language; Auditory-Verbal Therapy [ 102 ]; The 10-year-old Early Childhood Home Instruction Program for Hearing-Impaired Infants and Their Families [ 103 ]; PiCS Intervention using distance education technology [ 104 ]; A program for teaching written language [ 105 ]; HI CHIPS Total Communication Program [ 106 ]; Communication Program [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the learning of English will be through written texts, not through speech. That this can be an appropriate and successful method for the introduction of a spoken language has been argued by Paul and Gram ly (1986) and documented by Suzuki and Notoya (1984), who compared the acquisition of written and oral language in six deaf children from infancy to about the age of six. They report success at teaching reading before speaking and conclude that for deaf children (1984:10):…”
Section: Guiding Principlesmentioning
confidence: 93%